2017
DOI: 10.33394/j-lkf.v5i2.135
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Multimedia Flash pada Materi Energi untuk Meningkatkan Motivasi Belajar Siswa

Abstract: Title: Development of Flash Multimedia on Energy Materials to Improve Student Learning Motivation].This study aims to develop flash multimedia on energy materials to improve student learning motivation. This study is a development research with ADDIE model. Flash multimedia validation involves 2 validators (media experts and media design experts). Validation results show on the aspect of the material with a score of 3.6 with the category "high validity" and the media aspect with a score of 3.4 with the categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Based on the results of interviews with physics teachers in junior high school, it was observed that the factor that caused the low student learning outcomes was the lack of student understanding of the material concepts taught by subject teachers because during the learning process took place teachers used lecture and question and answer methods so the teaching and learning process monotonous, less interesting and boring and certainly becomes an option for educators to be able to stimulate learning activities again to reach the desired competency. Previous studies (Purnamasari et al, 2017;Sukroyanti & Sufianti, 2017;Sanjaya, 2002) found that learning physics in schools tends to be monotonous and boring so that it impacts on motivation and learning outcomes, especially critical thinking of students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of interviews with physics teachers in junior high school, it was observed that the factor that caused the low student learning outcomes was the lack of student understanding of the material concepts taught by subject teachers because during the learning process took place teachers used lecture and question and answer methods so the teaching and learning process monotonous, less interesting and boring and certainly becomes an option for educators to be able to stimulate learning activities again to reach the desired competency. Previous studies (Purnamasari et al, 2017;Sukroyanti & Sufianti, 2017;Sanjaya, 2002) found that learning physics in schools tends to be monotonous and boring so that it impacts on motivation and learning outcomes, especially critical thinking of students.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the description of the results of the study, it can be seen that the use of active learning models is student-centered and emphasizes the active construction of knowledge independently as an alternative solution to the improvement of students' learning outcomes in science especially physics. Physics which is the science that analyzes natural phenomena and the interactions that occur in them (Purnamasari et al, 2017) is very relevant to be taught using contextual learning (Asy'ari, 2017). This study aims to improve physics learning outcomes of SMP Negeri 3 Tanjung in the academic year 2017/2018 through the implementation of contextual approaches based on learning communities.…”
Section: Introductionmentioning
confidence: 99%